2022
DOI: 10.3389/fpsyg.2022.877561
|View full text |Cite
|
Sign up to set email alerts
|

Linking the trust of industrial entrepreneurs on elements of ecosystem with entrepreneurial success: Determining startup behavior as mediator and entrepreneurial strategy as moderator

Abstract: PurposeThis study aimed to apply “multi-criteria decision approach and attitude-change theory” to examine post-COVID-19 impact on entrepreneurial mindset by investigating the link between entrepreneurs social capital (trust on three elements of ecosystem i.e., experts & enterprises, media, and government) and entrepreneurial success (both individual and organizational). Specifically, this study analyzed entrepreneurs' dispositional factor (startup behavior) as an underlying mechanism to bridge trust an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 96 publications
0
4
0
Order By: Relevance
“…It can be concluded that if students have high financial literacy but they have low selfefficacy then this will result in these students not having good entrepreneurial behavior. Because the self-efficacy that students have will make or can encourage a student to have good entrepreneurial behavior too [50].…”
Section: The Influence Of Financial Literacy On Entrepreneurial Behav...mentioning
confidence: 99%
“…It can be concluded that if students have high financial literacy but they have low selfefficacy then this will result in these students not having good entrepreneurial behavior. Because the self-efficacy that students have will make or can encourage a student to have good entrepreneurial behavior too [50].…”
Section: The Influence Of Financial Literacy On Entrepreneurial Behav...mentioning
confidence: 99%
“…With all the governmental interventions GS can becomes beneficial to eliminate the market bias towards SMEs. Keeping this in view governments are establishing women’s chambers of commerce, ensuring that women entrepreneurs get all the facilities and support required to make their start-ups a success ( Rehman et al, 2022 ). It provides support for every women entrepreneur to ensure that their start-up smoothly becomes operational and starts making an economic contribution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Governments are increasingly establishing chambers of commerce for women to provide essential facilities and support for women entrepreneurs (Rehman et al, 2022). These initiatives offer comprehensive assistance to women entrepreneurs, facilitating a seamless transition into operational status and meaningful economic contributions.…”
Section: Government Policiesmentioning
confidence: 99%
“…Over past decades, there has been notable progress in women involvement in entrepreneurial endeavors, positively impacting national development (McCall & Mearns, 2021). However, women entrepreneurs still face challenges due to gender discrimination in the tourism sector (Ntanjana & Mangwane, 2019), which remains pervasive in many developing economies (Rehman et al, 2022). Additionally, limited access to financial resources, inadequate training, specific personality traits, and a lack of support from government and family members restrict women's ability to pursue entrepreneurship in developing countries (Chhabra et al, 2022).…”
Section: H1b Government Policies Positively Affect Success Of Women T...mentioning
confidence: 99%